Auditory distractors are processed but do not interfere with visual search of any difficulty when sound is irrelevant. - Mandal, Ananya; Röer, Jan Philipp; Liesefeld, Heinrich R. (Visual Cognition)
People often report being distracted during their visual tasks, such as monitoring the road ahead, by task-irrelevant sounds, for example, a baby crying on the backseat. When we first tried to study the effect of auditory distraction on visual-search performance in the laboratory using the highly sensitive additional-singleton paradigm – to our surprise – several types of auditory distractors reliably failed to cause any substantial interference. We explained these findings with a powerful attentional filtering mechanism that can shield visual search from interference by irrelevant sounds. In the present study, we examine conditions under which this mechanism might break down as suggested by insights from research on auditory distraction. It has been shown that whether an auditory distractor causes interference often hinges on the difficulty of the employed task. However, across three levels of search-task difficulty, we here reliably replicate the pattern we had observed before: At each difficulty level of Experiment 1, an unpredictably presented auditory distractor was processed to some extent (as indicated by an effect on the speed-accuracy tradeoff) but did not interfere with overall search performance. The same distractor reliably impeded search performance when the attentional shielding mechanism was experimentally disabled by a secondary task in Experiment 2.